2017
DOI: 10.1038/ng.3768
|View full text |Cite|
|
Sign up to set email alerts
|

Genome-wide association analysis identifies novel blood pressure loci and offers biological insights into cardiovascular risk

Abstract: Elevated blood pressure is the leading heritable risk factor for cardiovascular disease worldwide. We report genetic association of blood pressure (systolic, diastolic, pulse pressure) among UK Biobank participants of European ancestry with independent replication in other cohorts, and robust validation of 107 independent loci. We also identify new independent variants at 11 previously reported blood pressure loci. Combined with results from a range of in silico functional analyses and wet bench experiments, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
452
1
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 507 publications
(487 citation statements)
references
References 77 publications
19
452
1
5
Order By: Relevance
“…Our eQTL analysis identified 60 novel loci with eQTLs in arterial and 20 in adrenal tissue (Supplementary Table 9), substantially increasing those identified in our previously published GWAS on ~140K UKB individuals10. An example is SNP rs31120122 which defines an aortic eQTL affecting expression of the MED8 gene within the SZT2 locus.…”
Section: Resultsmentioning
confidence: 54%
“…Our eQTL analysis identified 60 novel loci with eQTLs in arterial and 20 in adrenal tissue (Supplementary Table 9), substantially increasing those identified in our previously published GWAS on ~140K UKB individuals10. An example is SNP rs31120122 which defines an aortic eQTL affecting expression of the MED8 gene within the SZT2 locus.…”
Section: Resultsmentioning
confidence: 54%
“…Furthermore, the GRS generated by combination of 107 loci by Warren et al [11] showed that the group with GRS in the lowest quintile had an SBP approximately 9–10 mm Hg lower than those with GRS in the highest quintile. Reductions in BP of such a magnitude might lead to significantly lower cardiovascular morbidity and mortality among hypertensive patients.…”
Section: Discussionmentioning
confidence: 99%
“…The latest GWAS by Warren et al [11] identified multiple loci involved in BP regulation, including angiotensin-converting enzyme, voltage-dependent calcium channel auxiliary subunit, metallo­endopeptidase/neutral endopeptidase, adrenergic β 2B receptor, and phosphodiesterase 5a. Moreover, in the pathway analysis, they also showed an enrichment of pathways associated with cardiovascular disease, including the α-adrenergic pathway, CXCR4 chemokine signaling pathway, endothelin system, and angiotensin-receptor pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Генетическая основа АГ включает в себя множество полиморфных локусов. Так, с помощью полногеномных исследований ассо-циаций (genome-wide association studies -GWAS) было выявлено более 100 генов различных сигналь-ных путей и еще больше однонуклеотидных поли-морфизмов (ОНП), ассоциированных с повышен-ным артериальным давлением и гипертонией [8][9][10]. Однако, несмотря на выявление на сегодняшний день большого количества генов и ОНП, ассоциированных с АГ, каждый в отдельности генетический вариант имеет слабое влияние на развитие АГ, объясняет очень малую долю наследственности в развитии заболевания и, таким образом, имеет ограниченную предсказатель-ную ценность [11].…”
unclassified